Implementasi Model Project Based Learning untuk Meningkatkan Hasil Belajar Tematik Terpadu Peserta Didik Sekolah Dasar - Budi Hariadi; Mansurdin Mansurdin (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research is caused by the teacher when the learning process conveys the subject matter directly that is not innovative to apply the model to trigger children's creativity. The teacher does not implemente a model that can stimulate active children in learning and solve problems to make products. This study aims to describe the Improvement of Integrated Thematic Learning Process of Theme 8 of Grade 5th with the Project Based Learning Model. The type of research is class action with qualitative and quantitative approaches. Research data is from the observations of the implementation of the learning process with the Project Based Learning model and the results of action after the learning process takes place. The study was in two cycles. One cycle consists of planning, implementation, observation, reflection. The research subjects were teachers and 22 students of Grade 5th elementary school that consists of 9 male and 13 female. The results of the first cycle of research for student learning outcomes has average value of 3.14 good category (GC) percentage of completeness 32%, in the second cycle increased to 3.75 excellent category (EC) percentage of completeness 95%.